Estimation of Genetic Variability, Heritability and Genetic Advance in Potato (Solanum tuberosum L.) Genotypes for Tuber Yield and Yield Related Traits - Awoke Ali Zeleke; Tiegist Dejene Abebe; Baye Berihun Getahun (Turkish Journal of Agriculture: Food Science and Technology)
Potato is a high potential food security crop in Ethiopia. Genetic variability is the basis of all crop improvement programs. The study was conducted at Adet in 2018 with the objective of assessing the extent and pattern of genetic variability of potato genotypes for yield and yield related traits. A total of 36 potato genotypes were evaluated for 18 quantitative traits in simple lattice design. The analysis of variance revealed that highly significant difference among the tested potato genotypes for all quantitative traits except stem number per hill. The phenotypic coefficient of variation was ranged from 4.56 to 56.01% (for specific gravity and unmarketable tuber yield ha-1 respectively) and the genotypic coefficient of variation was ranged from 2.32 to 40.66% (specific gravity and late blight severity percentage respectively). Days to attain 50% emergence, leaf area index, number of marketable and total tubers per plant, marketable and total tuber yield ha-1, and late blight severity percentage showed high heritability and high genetic advance as percent of mean. Most of the traits had high phenotypic coefficient of variation and genotypic coefficient of variation; and coupled high heritability with high genetic advance as percent of mean. Traits having high heritability and high genetic advance as percent of means is effective for simple selection.